Method for regulating pore structure of okara-based hard carbon negative electrode material by using protease, product and application thereof
Patent Information
- Application Number
- CN202610976386.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-02
AI Technical Summary
专利CN118270767B则指出,在常规生物质水热处理制备硬碳的过程中,会产生焦油等不利副产物,需要额外结合醇处理等步骤予以消除,增加了工艺的复杂性和成本
1. 以废弃豆渣为原料,采用酶辅助造孔策略替代传统化学造孔方法,避免了昂贵且有毒化学试剂的使用,显著降低化学污染与能耗,实现废弃物的资源化与高值化利用,契合绿色制造理念。
Smart Images

Figure CN122482441B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery materials technology, specifically to a method for regulating the pore structure of soybean residue-based hard carbon anode materials by protease regulation, as well as its products and applications. Background Technology
[0002] The continued growth in energy demand has made energy storage technology a research hotspot. While lithium-ion batteries have become the dominant energy storage battery, the limited availability of lithium resources restricts their large-scale application, making abundant and inexpensive sodium-ion batteries an important alternative. However, traditional graphite-based anodes suffer from slow insertion / extraction kinetics due to the large radius of sodium ions, limiting battery performance. Hard carbon materials, with their high specific surface area, good conductivity, and abundant porous structure, have become ideal candidates for current sodium-ion battery anode materials.
[0003] Constructing a reasonable pore structure in hard carbon is crucial. The ideal pore morphology should be dominated by micropores with a diameter of less than 2 nm, supplemented by an appropriate amount of mesopores of 2 to 10 nm, and the channels should form an open, interconnected network structure to balance high specific capacity and excellent rate performance. However, existing hard carbon pore-forming methods, such as plasma etching and chemical etching, although capable of controlling the microstructure, generally suffer from problems such as high energy consumption, cumbersome operation, and environmental pollution.
[0004] In recent years, enzyme-assisted pore-forming technology has provided a new approach for the sustainable preparation of hard carbon materials due to its environmentally friendly and mild processing characteristics. Meanwhile, soybean residue, as a byproduct of the food industry, is widely available, inexpensive, and rich in protein and carbohydrates, possessing the potential to serve as a precursor for hard carbon. Patent CN118529713A discloses a technical route for enzymatic hydrolysis of soybean residue using proteases, but its purpose is to reduce the content of proteins and other substances to a specific target range, without addressing the effective control of the pore structure of the final hard carbon material. Patent CN118270767B points out that in the conventional biomass hydrothermal treatment process for hard carbon preparation, undesirable byproducts such as tar are generated, requiring additional steps such as alcohol treatment to eliminate them, increasing the complexity and cost of the process. Therefore, a method for effectively controlling the pore structure of hard carbon anode materials using soybean residue as a biomass substrate is still lacking. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for regulating the pore structure of soybean residue-based hard carbon anode materials using proteases, along with the resulting products and applications. This invention employs a protease-assisted pore-forming method, using soybean residue as a carbon source, and obtains porous hard carbon anode materials through steps such as protease inoculation and hydrothermal treatment, and carbonization. These materials exhibit high-efficiency charge storage and transport capabilities, excellent cycle performance, and broad application prospects in the field of sodium-ion batteries.
[0006] This invention provides a method for regulating the pore structure of soybean residue-based hard carbon anode materials using proteases, comprising the following steps: (1) Mix soybean residue with deionized water to form a paste, preheat it with water bath and ultrasonic treatment, and then place it in a constant temperature environment and inoculate it with biological protease to carry out enzymatic hydrolysis. (2) After the enzymatically hydrolyzed material is mixed with deionized water, it is transferred to a hydrothermal reactor, sealed, and then subjected to hydrothermal reaction. (3) After the hydrothermal reaction product is filtered, washed and dried, it is carbonized under an inert atmosphere to obtain a porous hard carbon material. After acid washing, a soybean residue-based biomass porous hard carbon anode material is obtained.
[0007] The technical solution described in this invention uses soybean residue as raw material. First, at 30-70... Enzymatic hydrolysis with protease was performed in a constant temperature environment to construct a porous framework; then the pores were dehydrated and solidified in an oven; next, the precursor molecular structure was regulated using a hydrothermal reactor, and water-soluble trace elements such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), and zinc (Zn) were dissolved, while soluble small molecule peptides and amino acids were eluted; then, high-temperature carbonization was carried out in an inert atmosphere in a tube furnace to form a hard carbon matrix; finally, impurities were removed by acid washing to obtain high-purity porous biomass hard carbon anode material.
[0008] Preferably, in step (1), the soybean residue is derived from soybeans and their processed products, with a particle size of 3-75 μm and a protein content of 1%-80%, more preferably 1.5%-60%. Preferably, the soybean residue is obtained by crushing and sieving soybeans (preferably 200 mesh), or it is waste soybean residue formed after the expiration of soybean processed products. More preferably, the soybeans include, but are not limited to, seeds of legume plants that can produce soybean residue, such as soybeans, green soybeans, black soybeans, red soybeans, mung beans, and kidney beans. More preferably, the soybeans are selected from at least one of Zhonghuang 37 (protein content of 41.8-48.28%), Nandou No. 5 (protein content of 46.18-48.5%), and Qihuang 34 (protein content of 41.8-45.1%), and all the listed soybeans are applicable to this application; more preferably, the waste soybean residue can be waste soybean residue obtained by grinding the dried solids of at least one of the following: soy milk (protein content of about 1.8-3.5% before drying, protein content of about 44.68-50.65% after drying), tofu (protein content of about 4.8-8.2% before drying, protein content of about 45.32-55.35% after drying), or dried tofu (protein content of about 16.5-17.4% before drying, protein content of about 46.55-54.36% after drying); More preferably, the soybean residue is derived from soybeans; soybeans are put into a grinder and ground into soybean residue powder, which can pass through a 200-mesh sieve, and the average particle size distribution of the soybean residue is 3 ~ 75 μm.
[0009] Preferably, in step (1), the water bath heating involves dissolving soybean residue in deionized water and then bathing it in a water bath for a period of time under conditions such as a forced-air drying oven, a hydrothermal oven, or a water bath. The purpose of water bath heating is to utilize thermodynamic driving forces to break non-covalent bonds such as hydrogen bonds within and between protein molecules, causing the originally tightly folded three-dimensional protein structure to unfold, allowing the protein molecular chains to fully unfold. After the protein structure unfolds in this way, the enzyme cleavage sites originally embedded inside the molecule are exposed to the molecular surface, thereby significantly increasing the accessibility of subsequent proteases and substrates, creating favorable conformational conditions for efficient protease cleavage. After water bath heating pretreatment, the enzymatic hydrolysis efficiency and degree of hydrolysis of proteins can be significantly improved, which is conducive to the subsequent generation of more small molecule peptides and amino acid precursors, thereby improving the pore structure and electrochemical performance of the final hard carbon material.
[0010] Preferably, the water bath temperature in step (1) is 60~100℃ and the heating time is 15~30 minutes.
[0011] Preferably, in step (1), the mass concentration of the mixture of soybean residue and deionized water is controlled at 5 to 15%.
[0012] Preferably, in step (1), the ultrasonic frequency of the ultrasonic treatment is 20,000 to 50,000 Hz; the ultrasonic power is 100 to 600 W; and the ultrasonic time is 25 to 35 min. The purpose of ultrasonic treatment is to utilize the acoustic cavitation effect generated by ultrasound in a liquid medium to form a large number of tiny bubbles that instantly generate and violently collapse. The resulting local microjets and shear forces can exert a strong physical dispersion and deagglomeration effect on the raw material particles and protein macromolecules. This physical effect can effectively separate and unfold the entangled and aggregated protein molecular chains, exposing more enzyme cleavage sites, while enhancing the dispersibility and uniformity of proteins in the aqueous phase, providing a more sufficient substrate contact area for the subsequent efficient enzymatic cleavage of proteases. Ultrasonic treatment and water bath heating can be used alone or in combination. The synergy of the two can further enhance the unfolding effect of proteins and improve the enzymatic hydrolysis efficiency and degree of hydrolysis.
[0013] Preferably, in step (1), the degree of hydrolysis of the material after enzymatic hydrolysis is ≥80%, and the degree of hydrolysis is preferably measured in real time using the pH-stat method. Preferably, the protein content after enzymatic hydrolysis is no more than 10%, preferably 5~10%.
[0014] Preferably, in step (1), the inoculation of biological protease is performed by sequentially inoculating flavor protease ( Flavourzyme) and alkaline protease ( Alkaline proteinase More preferably, the buffer system for the flavor protease is: acetic acid-sodium hydroxide (C2H4O2-NaOH), the hydrolysis temperature is 30~70℃ and the hydrolysis pH is 5~7, and the ratio of enzyme activity units to the weight of dried soybean residue is 2000U~4000U:1g. Since hydrolysis causes the peptide bonds of proteins to break and decompose into amino acids and small peptides, releasing protons, which leads to a decrease in pH, a low concentration of NaOH solution needs to be added in real time to maintain pH stability. Then, the stirring time is 1~6 hours at a speed of 200 r / min, and then the pH is adjusted to alkaline to inactivate the flavor protease. The buffer system for the alkaline protease is: glycine-sodium hydroxide (C2H5NO2-NaOH). In addition to obtaining free glycine through the hydrolysis of the flavor protease, some glycine needs to be added to form a stable buffer system. The hydrolysis temperature is 30~70℃ and the hydrolysis pH is 7~ 10. The ratio of protease activity units to the weight of dried soybean residue is 2000U~4000U: 1g. The stirring time is 1~6 hours, and the stirring speed is 200 r / min. During the stirring process, a low concentration of NaOH solution needs to be added in real time to maintain pH stability. After the reaction is complete, the enzyme is inactivated, and the pH is adjusted to neutral 7. More preferably, the enzyme is inactivated in a 90~100℃ forced-air drying oven for 10~30 minutes. More preferably, the pH is adjusted by hydrochloric acid and / or sodium hydroxide solution.
[0015] More preferably, specifically: the temperature of the paste mixture obtained in step (1) is adjusted to 30-70℃, the buffer system is acetic acid-sodium hydroxide (C2H4O2-NaOH), and the pH of the system is adjusted to 5-7. Flavor protease is added, the culture medium is the protein in the paste mixture, and the enzyme activity unit: the ratio of dried soybean residue is 2000-4000U: 1g. The stirring time is 1-6h, the rotation speed is 200r / min, and 0.1-1mol / L NaOH solution needs to be continuously added during the reaction. The enzyme is inactivated in a 90-100℃ forced-air drying oven for 10-30 minutes. Then the temperature is adjusted to 30-70℃, the buffer system is glycine-sodium hydroxide (C2H5NO2-NaOH), and the pH of the system is adjusted to 7-10. Alkaline protease is added, and the culture medium is the protein and small molecule peptides remaining from the previous step, and the enzyme activity unit: the ratio of dried soybean residue is 2000-4000U: 1g, stirring time is 1~6h, speed is 200r / min, during the reaction process, 0.1~1mol / L NaOH solution needs to be added dropwise continuously, inactivate enzyme in a 90~100℃ forced air drying oven for 10~30 minutes, and adjust pH to 7.
[0016] In this invention, the flavor protease exerts its synergistic endonuclease and exonuclease effects, gently dissecting the protein from the surface and ends, loosening the original soybean residue protein structure and exposing more internal cleavage sites. This creates favorable conformational conditions for the subsequent efficient endonuclease action of the alkaline protease. The acetate-sodium hydroxide buffer provides a mildly acidic to neutral environment, while its acetate ions decompose and volatilize during subsequent high-temperature processing, without introducing additional solid impurities. The alkaline protease exerts its highly efficient endonuclease activity, deeply hydrolyzing the numerous cleavage sites exposed in the first step, efficiently degrading the protein into small peptides and amino acids. Furthermore, glycine itself is an amino acid, and no other impurities or solid contaminants are introduced.
[0017] Preferably, in step (2), the weight ratio of the enzymatically hydrolyzed material (oven-dry weight) to deionized water is approximately 1:1 to 1:5; more preferably, the oven-dry weight is obtained by weighing the enzymatically hydrolyzed material after drying; even more preferably, the drying temperature is 70 to 120°C. ℃; drying time: 1 ~ 5 days. More preferably, drying is carried out under the conditions of a forced-air drying oven; And / or, the hydrothermal reaction temperature is 120 ~ 180℃, and the hydrothermal reaction time is 5 ~ 15 hours.
[0018] Preferably, in step (3), the hydrothermal reaction product is filtered, washed with deionized water and / or anhydrous ethanol, and then placed in a forced-air drying oven to dry; And / or, the drying temperature is: 70 ~ 100 ℃; drying time: 1 ~ 5 days.
[0019] Preferably, in step (3), the residual protein and polypeptide in the dried hydrothermal reaction product account for 5 to 10% of the total mass.
[0020] Preferably, in step (3), the inert atmosphere is at least one of argon, nitrogen and / or helium; And / or, the heating rate for carbonization is: 2 ~ 10 ℃ / min; Insulation temperature: 1200 ~ 1500℃; Insulation time: 60 ~ 240 minutes.
[0021] Preferably, in step (3), the acid solution for pickling is hydrochloric acid; the solution concentration is 0.8 mol / L ~ 1.2 mol / L; the pickling time is 8 ~ 12 hours; and the ratio of carbonization product to acid solution is preferably 1 g / mL.
[0022] More preferably, pickling involves mixing and soaking the carbonized product with a hydrochloric acid solution, followed by washing with deionized water until neutral.
[0023] More preferably, the product is dried after washing at a temperature of 70~120°C. ℃; drying time: 12 hours, preferably using a forced-air drying oven.
[0024] Preferably, the method specifically includes the following steps: S1. Add soybean residue to deionized water to prepare a mass concentration of 5-15%, and heat at 60-100℃ for 15-30 minutes; subject the resulting paste mixture to ultrasonic treatment at a frequency of 30000-50000Hz, a power of 100-300W, and a duration of 25-35 minutes. S2. Adjust the temperature of the paste mixture obtained in step S1 to 30-70℃ and the pH to 5-7, add flavor protease, with an enzyme activity unit: the ratio of dried soybean residue to 2000-4000U: 1g, stir for 1-6 hours, and inactivate the enzyme in a 90-100℃ forced-air drying oven for 10-30 minutes; then adjust the temperature to 30-70℃ and the pH to 7-10, add alkaline protease, with an enzyme activity unit: the ratio of dried soybean residue to 2000-4000U: 1g, stir for 1-6 hours, inactivate the enzyme in a 90-100℃ forced-air drying oven for 10-30 minutes, and adjust the pH to neutral; S3. After drying the enzymatically hydrolyzed material, add deionized water at a weight ratio of 1:1 to 1:5, stir evenly, transfer to a hydrothermal reactor, seal, and carry out hydrothermal reaction at 120 to 180°C for 5 to 15 hours. S4. After filtering, washing and drying the hydrothermal reaction product, the temperature is raised to 1200-1500℃ at a rate of 2-10℃ / min under an inert atmosphere and held for 60-240 minutes for carbonization. After acid washing and drying, porous hard carbon anode material is obtained.
[0025] Preferably, the specific surface area of the prepared porous hard carbon anode material is 3 to 40 m². 2 / g; pore size distribution is mainly concentrated in 0.3 ~ 10nm; pore volume distribution is mainly concentrated in 0.01 ~ 0.5cm³ 3 / g; average particle size distribution is 1 ~ 20μm.
[0026] The present invention also provides a soybean residue-based biomass hard carbon anode material prepared by any of the above methods.
[0027] The present invention also provides an application of soybean residue-based biomass hard carbon anode material prepared by any of the above methods in the field of sodium-ion batteries.
[0028] In this invention, the core role of protease hydrolysis is to assist in pore formation. By controlling the hydrolysis conditions, protease is used to specifically decompose proteins in soybean residue, forming a rich pore structure in situ during subsequent hydrothermal treatment and carbonization. In the embodiments of this invention, the protein content of the soybean residue after enzymatic hydrolysis is no higher than 10%, achieving excellent pore-forming effects. This further proves that the hydrolysis effect of this invention is not simply content regulation, but rather based on the template or activation effect of protein decomposition products on the carbon skeleton structure, thereby achieving effective control of the pore structure. Simultaneously, this invention creatively adopts a process route of enzymatic hydrolysis followed by hydrothermal treatment. Through enzymatic pretreatment, the proteins and other components in the soybean residue are pre-decomposed into small molecule peptides or amino acids. Most of these small molecule peptides and amino acids have good water solubility and can be effectively separated with the liquid phase during subsequent filtration, thus significantly reducing the generation of large molecular byproducts such as tar during the hydrothermal stage. At the same time, some small molecule peptides and amino acids remaining in the solid phase can undergo structural reconstruction during the hydrothermal process. These small molecule precursors undergo recombination and self-coating around the pores created by in-situ hydrolysis of proteases, along the pore wall surface. This not only preserves the abundant sodium storage active sites inside, but also improves the material's initial coulombic efficiency and structural stability through the moderately narrowed pore openings.
[0029] The aforementioned synergistic effect transforms hydrothermal treatment from a process that may have adverse effects in existing technologies into a process that facilitates precise control of pore structure and orderly construction of the carbon framework. This simplifies the process and achieves a technological breakthrough by eliminating the need for additional processing steps. Furthermore, this invention uses waste soybean residue as a carbon source, which not only achieves effective utilization of waste and reduces raw material costs but also has environmentally friendly characteristics. The porous hard carbon anode material prepared by the above method has efficient charge storage and transport capabilities, as well as excellent cycle performance. When applied to sodium-ion battery anodes, it exhibits superior electrochemical performance, meeting the demands for high-performance batteries in large-scale energy storage, electric vehicles, portable electronic devices, and other fields.
[0030] This invention not only provides a novel protease-assisted pore-forming method and the prepared material, but more importantly, through a renewed understanding of the enzymatic hydrolysis mechanism and innovative design of the process route, it overcomes many shortcomings in the existing technology, opening up a new path for the development of hard carbon anode materials for sodium-ion batteries. This is of great significance for promoting green energy development and sustainable development.
[0031] Based on the above technical solution, compared with the prior art, the present invention has the following beneficial effects: 1. Using waste soybean residue as raw material, an enzyme-assisted pore-forming strategy is adopted to replace the traditional chemical pore-forming method, avoiding the use of expensive and toxic chemical reagents, significantly reducing chemical pollution and energy consumption, realizing the resource utilization and high-value utilization of waste, which is in line with the concept of green manufacturing.
[0032] 2. The raw material is agricultural waste, which is widely available and inexpensive, thus realizing the high-value transformation of soybean residue.
[0033] 3. This invention introduces hydrothermal treatment, which effectively removes soluble trace elements (such as Na, K, Ca, Mg, Zn, etc.), most of the soluble small molecule peptides and amino acids produced by enzymatic hydrolysis, and the previously present soluble small molecule hydrocarbons from the precursor after enzyme-assisted pore formation. This ensures the uniformity of the precursor's chemical composition and microstructure, thereby obtaining a hard carbon material with highly controllable structure. At the same time, this step avoids the condensation of small molecule hydrocarbons into tar during the high-temperature carbonization stage, reducing the risk of gas path blockage.
[0034] Furthermore, this invention utilizes an enzyme-assisted pore-forming mechanism, which has advantages such as low cost and environmental friendliness, and has broad application prospects in the field of sodium-ion batteries. Attached Figure Description
[0035] Figure 1 SEM images of the hard carbon anode material prepared in Example 1; Figure 2 SEM image of the hard carbon anode material prepared in Comparative Example 4; Figure 3 SEM images of the precursor prepared in Example 1; Figure 4 SEM image of the hard carbon anode material prepared in Comparative Example 1; Figure 5 SEM image of the hard carbon anode material prepared in Comparative Example 2; Figure 6 SEM image of the hard carbon anode material prepared in Comparative Example 3; Figure 7 SEM image of the hard carbon anode material prepared in Comparative Example 5; Figure 8 XRD images of the hard carbon anode material prepared in Example 1; Figure 9 Comparison graph of the cycle capacity of sodium-ion batteries assembled with hard carbon anode materials prepared in Examples 1, 2, 3 and 4 under different rate conditions. Figure 10 Comparison graph of coulombic efficiency of sodium-ion batteries assembled with hard carbon anode materials prepared in Examples 1, 2, 3 and 4 under different rate conditions. Figure 11 The cyclic stability graph for Example 1 is shown. Figure 12 The image shows the coulombic efficiency diagram for the cyclic stability of Example 1. Detailed Implementation
[0036] To better understand the purpose, process, and advantages of this invention, specific embodiments and accompanying drawings are provided below to further describe the technical solutions and implementation methods of this invention clearly, completely, and in detail. It should be understood that the embodiments described herein are implemented based on the technical solutions of this invention, providing detailed implementation methods and specific operating procedures. However, these are only some embodiments of this invention, not all embodiments. The described implementation methods are limited to illustrating and explaining this invention and do not constitute a limitation thereof. All other implementation methods obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0037] Unless otherwise specified, the experimental methods and conditions used in the embodiments of this invention are conventional methods and conditions. The materials, reagents, instruments, and equipment used in the embodiments, unless otherwise specified, are all conventional substances or equipment known to those skilled in the art and can be obtained commercially or prepared by conventional methods. The reaction conditions described in the invention's content can all achieve the stated reactions and obtain the desired products. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of this invention.
[0038] Example 1 (1) 54g of dried soybeans (Zhonghuang 37 purchased from Jining Shengyuan Seed Industry Co., Ltd.) were put into a pulverizer and passed through a 200-mesh sieve. The average particle size distribution was 3 ~ 75μm. (2) The obtained dried soybean residue was tested and found to have a protein content of about 45.36% (measured by near-infrared spectroscopy). It was then added to deionized water at a mass concentration of 10% and heated in a water bath at 95°C for 20 minutes. (3) The paste mixture obtained in step (2) is subjected to ultrasonic treatment; the ultrasonic frequency is 40000Hz; the ultrasonic power is 200W; and the ultrasonic time is 30min. (4) Quickly adjust the temperature of the paste mixture to 50°C, and add a buffer system of acetic acid-sodium hydroxide (C2H4O2-NaOH), adjust the pH to 6.5, add flavor protease (purchased from Hangzhou Fangping Chemical Co., Ltd., CAS No. 9001-92-7), the enzyme activity unit: the ratio of dried soybean residue is 3000U: 1g, the stirring time is 3.5 h, the speed is 200r / min, and 0.2 mol / L NaOH solution needs to be added dropwise continuously during the reaction. Then, after inactivating the enzyme in a 95℃ forced-air drying oven for 15 minutes, the temperature was quickly adjusted to 50℃, and an additional 2.25g of glycine was added to form a glycine-sodium hydroxide (C2H5NO2-NaOH) buffer system. The pH was adjusted to 9, and alkaline protease (purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS No. 9014-01-1) was added. The enzyme activity unit: the ratio of dried soybean residue was 3000U: 1g. The stirring time was 3.5h, and the enzyme was inactivated in a 95℃ forced-air drying oven for 15 minutes. The pH was then adjusted to 7. (5) The enzymatically hydrolyzed material (the degree of hydrolysis was determined to be approximately 90.51%, and the method for determining the degree of hydrolysis was pH-stat method) was dried in a 90℃ forced-air drying oven for 2 days; (6) Add the dried material from step (5) to deionized water at a weight ratio of 1:2, stir evenly, transfer it to a hydrothermal reactor with a container filling degree of 75%, seal it and carry out hydrothermal reaction, maintain the temperature at 150℃, keep it warm for 10 hours, and finally obtain the hydrothermally treated powder precursor. (7) Filter the hydrothermal product, wash it three times with deionized water and once with anhydrous ethanol, and then transfer it to an 80°C container. After drying in a forced-air drying oven at ℃ for 24 hours, the residual protein and polypeptide content was determined to be approximately 7.62% of the total mass. (8) The treated precursor is heated in an argon atmosphere for carbonization at a heating rate of 2. The temperature was increased to 1300℃ at ℃ / min and held for 3 hours to obtain soybean residue-based biomass hard carbon anode material. (9) Soak the soybean residue-based biomass hard carbon anode material in hydrochloric acid solution (the hydrochloric acid concentration is prepared to be 0.8 mol / L, and the weight ratio of hard carbon to hydrochloric acid is 1:1) for 10 hours, and then wash it with deionized water until it is neutral. (10) The above product is treated with 120 The soybean residue-based biomass hard carbon anode material was obtained by drying in a forced-air drying oven at ℃ for 12 hours.
[0039] Example 2 The soybean residue source of Example 1 was changed to Qihuang 34, which has a protein content of about 43.21% and a degree of hydrolysis of about 89.63%. The actual test showed that the residual protein and polypeptide accounted for 7.31% of the total mass, and the rest was the same as in Example 1.
[0040] Example 3 The soybean residue from Example 1 was changed to Nan Dou No. 5, which has a protein content of about 43.21% and a degree of hydrolysis of about 89.24%. The actual test showed that the residual protein and polypeptide accounted for 8.78% of the total mass, and the rest was the same as in Example 1.
[0041] Example 4 The source of soybean residue in Example 1 was changed to the solid residue obtained after drying waste soybean milk (from the kitchen of Zhejiang University of Technology). The solid residue was then ground by a grinder to obtain waste soybean residue. The protein content was tested to be about 45.23%, the degree of hydrolysis was about 86.87%, and the actual tested residual protein and peptides accounted for about 9.84% of the total mass. The rest was the same as in Example 1.
[0042] Example 5 The source of soybean residue in Example 1 was changed to the solid residue obtained after drying waste tofu (from the kitchen of Zhejiang University of Technology). The solid residue was then ground by a grinder to obtain waste soybean residue. The protein content was tested to be about 45.59%, the degree of hydrolysis was about 87.31%, and the actual tested residual protein and peptides accounted for about 9.78% of the total mass. The rest was the same as in Example 1.
[0043] Example 6 The source of soybean residue in Example 1 was changed to the solid residue obtained after drying waste dried soybeans (from the kitchen of Zhejiang University of Technology). The solid residue was then ground by a grinder to obtain waste soybean residue. The protein content was tested to be approximately 46.68%, the degree of hydrolysis was approximately 87.56%, and the actual tested residual protein and polypeptides accounted for approximately 9.92% of the total mass. The rest was the same as in Example 1.
[0044] Example 7 The enzymatic hydrolysis temperature of the flavor protease in Example 1 was increased to 70 °C, and the rest was the same as in Example 1.
[0045] Example 8 The enzymatic hydrolysis temperature of the flavor protease in Example 1 was reduced to 40 °C, and the rest was the same as in Example 1.
[0046] Example 9 The alkaline protease hydrolysis temperature of Example 1 was increased to 70 °C, and the rest was the same as in Example 1.
[0047] Example 10 The alkaline protease hydrolysis temperature of Example 1 was lowered to 40 °C, and the rest was the same as in Example 1.
[0048] Example 11 The hydrothermal temperature of Example 1 was increased to 180 °C, and the rest was the same as in Example 1.
[0049] Example 12 The hydrothermal temperature of Example 1 was reduced to 120 °C, and the rest was the same as in Example 1.
[0050] Example 13 The sintering temperature of Example 1 was increased to 1500°C. ℃, the rest is the same as in Example 1.
[0051] Example 14 The sintering temperature of Example 1 was reduced to 1200°C. ℃, the rest is the same as in Example 1.
[0052] Example 15 The enzyme activity units of the flavor protease inoculated in Example 1 were increased to the weight ratio of dried soybean residue to 4000 U: 1g, with the rest remaining the same as in Example 1.
[0053] Example 16 The enzyme activity units of the flavor protease inoculated in Example 1 were reduced to 2000 U: 1g by weight of dried soybean residue, with the rest remaining the same as in Example 1.
[0054] Example 17 The enzyme activity unit of the alkaline protease inoculated in Example 1 was increased to the weight ratio of dried soybean residue to 4000 U: 1g, and the rest was the same as in Example 1.
[0055] Example 18 The enzyme activity units of alkaline protease inoculated in Example 1 were reduced to the weight ratio of dried soybean residue to 2000 U: 1g, with the rest remaining the same as in Example 1.
[0056] Example 19 The stirring time of the inoculated flavor protease in Example 1 was increased to 6 h, and the rest was the same as in Example 1.
[0057] Example 20 The stirring time of the inoculated flavor protease in Example 1 was reduced to 2 h, and the rest was the same as in Example 1.
[0058] Example 21 The stirring time for the alkaline protease inoculated in Example 1 was increased to 6 h, and the rest was the same as in Example 1.
[0059] Example 22 The stirring time for the alkaline protease inoculated in Example 1 was reduced to 2 h, and the rest was the same as in Example 11.
[0060] Example 23 The pH value of the flavor protease from Example 1 was increased to 7, and the rest was the same as in Example 1.
[0061] Example 24 The pH of the flavor protease from Example 1 was lowered to 6, and the rest was the same as in Example 1.
[0062] Example 25 The pH value of the alkaline protease in Example 1 was increased to 10, and the rest was the same as in Example 1.
[0063] Example 26 The pH value of the alkaline protease in Example 1 was lowered to 8, and the rest was the same as in Example 1.
[0064] Comparative Example 1 No enzymatic hydrolysis is performed, as follows: (1) 54g of soybeans (Zhonghuang 37 purchased from Jining Shengyuan Seed Industry Co., Ltd.) were put into a pulverizer and passed through a 200-mesh sieve. The average particle size distribution was 3 ~ 75μm. (2) Add soybean residue to deionized water at a weight ratio of 1:2, stir evenly, transfer it to a hydrothermal reactor with a container filling degree of 75%, seal it and carry out hydrothermal reaction, keep the temperature at 150℃, keep it warm for 10 hours, and finally obtain the hydrothermally treated powder precursor. (3) Filter the hydrothermal product, wash it three times with deionized water and once with anhydrous ethanol, and then transfer it to an 80°C container. Dry in a forced-air drying oven at ℃ for 24 hours; (4) The treated precursor is heated in an argon atmosphere for carbonization at a heating rate of 2. The temperature was increased to 1300℃ at ℃ / min and held for 3 hours to obtain soybean residue-based biomass hard carbon anode material. (5) Soak the soybean residue-based biomass hard carbon anode material in hydrochloric acid solution (hard carbon: hydrochloric acid in a weight ratio of 1:1, and the concentration of hydrochloric acid is 0.8 mol / L) for 10 hours, and then wash it with deionized water until neutral. (6) The above product is treated with 120 The material was dried in a forced-air drying oven at ℃ for 12 hours to obtain hard carbon anode material.
[0065] Comparative Example 2 Conventional chemical pore-forming methods are as follows: (1) 54g of soybeans (Zhonghuang 37 purchased from Jining Shengyuan Seed Industry Co., Ltd.) were put into a pulverizer and passed through a 200-mesh sieve. The average particle size distribution was 3 ~ 75μm. (2) Add 50g of dry powder to 500ml of deionized water and stir to form a solution. Then, add 5g of ZnCl2 as a chemical pore-forming agent for etching and stir for 12h. (3) Dry the etched material in a 90 ℃ forced-air drying oven for 24 hours; (4) Add the dried material to deionized water at a weight ratio of 1:2, stir evenly, transfer it to a hydrothermal reactor with a container filling degree of 75%, seal it and carry out hydrothermal reaction, keep the temperature at 150℃, keep it for 10 hours, and finally obtain the hydrothermally treated powder precursor. (5) Filter the hydrothermal product, wash it three times with deionized water and once with anhydrous ethanol, and then transfer it to an 80°C container. Dry in a forced-air drying oven at ℃ for 24 hours; (6) The treated precursor is heated in an argon atmosphere for carbonization at a heating rate of 2. The temperature was increased to 1300℃ at ℃ / min and held for 3 hours to obtain soybean residue-based biomass hard carbon anode material. (7) Soak the soybean residue-based biomass hard carbon anode material in hydrochloric acid solution (hard carbon: hydrochloric acid in a weight ratio of 1:1, and the concentration of hydrochloric acid is 0.8 mol / L) for 10 hours, and then wash it with deionized water until neutral. (8) The above product was dried in a 120°C forced-air drying oven for 12 hours to obtain hard carbon anode material.
[0066] Comparative Example 3 Example 1 did not involve the hydrothermal step; otherwise, it was the same as Example 1.
[0067] Comparative Example 4 Comparative Example 1 did not undergo a hydrothermal step, but was otherwise the same as Comparative Example 1.
[0068] Comparative Example 5 Comparative Example 2 did not undergo a hydrothermal step, but was otherwise the same as Comparative Example 2.
[0069] Comparative Example 6 Example 1 was inoculated with flavor protease only, and the rest was the same as in Example 1.
[0070] Comparative Example 7 Example 1 involved inoculating only the flavor protease and did not include the hydrothermal step; otherwise, it was the same as Example 1.
[0071] Comparative Example 8 In Example 1, only alkaline protease was inoculated; the rest was the same as in Example 1.
[0072] Comparative Example 9 Example 1 involved inoculation with alkaline protease but without the hydrothermal step; otherwise, it was the same as Example 1.
[0073] Comparative Example 10 The enzyme activity unit of the flavor protease inoculated in Example 1 was increased to the weight ratio of the material to 10000 U: 1g, and the rest was the same as in Example 1.
[0074] Comparative Example 11 The enzyme activity unit of the flavor protease inoculated in Example 1 was reduced to the weight ratio of the material to 1000 U: 1g, and the rest was the same as in Example 1.
[0075] Comparative Example 12 The enzyme activity unit of alkaline protease inoculated in Example 1 was increased to the weight ratio of the material to 10000 U: 1g, and the rest was the same as in Example 1.
[0076] Comparative Example 13 The enzyme activity unit of the flavor protease inoculated in Example 1 was reduced to the weight ratio of the material to 1000 U: 1g, and the rest was the same as in Example 1.
[0077] Comparative Example 14 The enzymatic hydrolysis time of the flavor protease inoculated in Example 1 was shortened to half an hour, and the rest was the same as in Example 1.
[0078] Comparative Example 15 The enzymatic hydrolysis time of the flavor protease inoculated in Example 1 was extended to 24 hours, and the rest was the same as in Example 1.
[0079] Comparative Example 16 The enzymatic hydrolysis time of the alkaline protease inoculated in Example 1 was shortened to half an hour, and the rest was the same as in Example 1.
[0080] Comparative Example 17 The enzymatic hydrolysis time of the alkaline protease inoculated in Example 1 was extended to 24 hours, and the rest was the same as in Example 1.
[0081] Comparative Example 18 The order of hydrothermal and enzymatic hydrolysis in Example 1 is reversed, and the rest is the same as in Example 1.
[0082] Comparative Example 19 The order of the flavor protease and alkaline protease in Example 1 was reversed, and the degree of hydrolysis was approximately 75.63%. The actual tested residual protein and peptide mass accounted for approximately 18.53% of the total mass, and the rest was the same as in Example 1.
[0083] Comparative Example 20 The flavor protease and alkaline protease in Example 1 were replaced with neutral protease. The buffer system was Tris-HCl, and the pH was adjusted to 7. The enzyme activity unit: the ratio of dried soybean residue was 4000U: 1g. The stirring time was 3.5 h, the stirring speed was 200 r / min, and the enzymatic hydrolysis temperature was 45℃. During the reaction, a 0.2 mol / L NaOH solution was continuously added dropwise. The degree of hydrolysis was approximately 50.63%, and the actual measured residual protein and peptide mass accounted for approximately 28.77% of the total mass. The rest was the same as in Example 1.
[0084] Test Example: Battery Assembly and Anode Material Performance Testing Examples 1 to 26 and Comparative Examples 1 to 20 were analyzed by BET and SEM tests. As shown in Table 1, the sample with the best performance had a more suitable specific surface area, average pore size, pore volume, ratio of micropores to macropores and average particle size.
[0085] Hydrothermal pretreatment plays a crucial role in regulating the carbon framework structure. Samples without hydrothermal treatment (after enzymatic hydrolysis) showed increased specific surface area and pore volume, indicating that hydrothermal pretreatment effectively removes loosely structured low-molecular-weight peptides and amino acids generated during enzymatic hydrolysis. These components are prone to uncontrolled pyrolysis and volatilization during high-temperature carbonization, leading to carbon framework structural disorder and pore collapse. After hydrothermal treatment, some of these unstable components are removed in advance, allowing the carbon framework to maintain structural integrity during subsequent carbonization. The remaining small-molecule peptides and amino acids in the solid phase undergo structural reconstruction around the pores created by in-situ protease hydrolysis, orderly reorganizing along the pore wall surface and self-encapsulating, gradually forming a semi-closed pore structure. This structure retains abundant sodium-storing active sites and improves the material's initial coulombic efficiency and structural stability through moderately narrowed pore openings, thereby achieving controllable construction of the pore structure and stable regulation of the specific surface area, ultimately yielding a hard carbon anode material with a regular microstructure.
[0086] It should be noted that the existing technology CN118270767B believes that hydrothermal treatment will produce undesirable byproducts such as tar, while the hydrothermal pretreatment in this invention effectively avoids tar formation and plays a positive role in stabilizing the carbon skeleton and regulating the pore structure. This difference indicates that the hydrothermal mechanism of this invention is substantially different from that of the existing technology, and the reversal of effects is attributed to the enzymatic hydrothermal synergistic process adopted in this invention: the protease pre-hydrolyzes large protein molecules into small peptides and amino acids. Some of these small molecule products are effectively removed in the subsequent solid-liquid separation process, thereby eliminating the precursors for tar formation at the source; the remaining small molecules undergo structural reconstruction during the hydrothermal process, forming a semi-closed structure by self-encapsulation around the pores created by enzymatic hydrolysis. The above dual effects together achieve a technological breakthrough against the opposite effects of the existing technology.
[0087] Table 1 Physicochemical properties of the examples and comparative examples
[0088] Preparation of hard carbon anode material: The hard carbon anode material, conductive carbon black (Super P, particle size 40 nm, purity >99.9%, Aladdin), and polyvinylidene fluoride (PVDF, particle size 5 μm, purity >99.9%, Aladdin) obtained in the above examples and comparative examples were accurately weighed according to a mass ratio of 8:1:1. These were then placed in N-methylpyrrolidone (NMP, analytical grade, purity >99.0%, Aladdin), ensuring a solid-liquid ratio of 1:4. Next, the mixture was transferred to a homogenizer and homogenized at 1600 r / min. After homogenization, 1 g of the resulting slurry was uniformly coated onto an aluminum foil current collector using a 200 μm scraper, ensuring an active material loading of 1-2 mg / cm³. -2 Subsequently, the coated aluminum foil was first dried in a 70°C forced-air drying oven for 2 hours, and then transferred to a 120°C vacuum drying oven for another 12 hours. After the drying process, the resulting electrode sheet was compacted on a roller press. Finally, the compacted electrode sheet was cut into 12 mm diameter pieces to serve as electrode plates.
[0089] Sodium-ion battery assembly: In a glove box filled with argon gas and with humidity and oxygen concentration below 0.01 ppm, the positive electrode shell, electrode plates, electrolyte (1 mol / L NaPF6 in DME, NaPF6 electrolyte (NP-035)), glass fiber separator (Whatman GF / D), sodium plate, gasket, spring, and negative electrode shell were assembled sequentially. Finally, the assembly was completed at 650 kg / cm³. -2 Encapsulation is performed under pressure.
[0090] Place the assembled sodium-ion battery on the Xinwei battery tester and test it at a rate of 0.02A g within the voltage range of 0.01~2.5 V. -1 Activate for three cycles, then use 0.2 A g. -1 Long-cycle testing was conducted. The rate testing used a 0.02A g... -1 0.04Ag -1 0.1A g -1 0.2A g -1 0.4A g -1 1A g -1 2A g -1 and 0.02A g -1 Current density.
[0091] like Figure 9As shown, the hard carbon anode material obtained in Example 1 at 0.02A g -1 0.04A g -1 0.1A g -1 0.2A g -1 0.4A g -1 1A g -1 2A g -1 and 0.02A g -1 The specific capacitance at the current density is 366.41 mA hg. -1 277.25mA hg -1 261.91mA hg -1 252.47mA hg -1 241.93mA hg -1 216.95mA hg -1 172.79mA hg -1 and 244.74 mA hg -1 The performance of Examples 2-26 showed the same trend as that of Example 1. Comparative Examples 1-20, except for those with excessively high protease ratios and excessive time, were significantly inferior to the examples. Specific electrochemical performance is shown in Table 2.
[0092] Table 2 Electrochemical performance of the examples and comparative examples
[0093] Analysis of the data in Table 2 shows that the type of protease, enzymatic hydrolysis conditions, hydrothermal temperature, carbonization temperature, and the order of each step have a decisive influence on the electrochemical performance of the final hard carbon material.
[0094] This invention employs a stepwise enzymatic hydrolysis scheme, first using flavor protease and then alkaline protease. In the first step, under flavor protease conditions, synergistic endonucleases and exonucleases gently dissociate the protein from the surface and ends, loosening the originally compact protein structure of soybean residue and exposing more internal cleavage sites. In the second step, under alkaline protease conditions, highly efficient endonucleases deeply hydrolyze the exposed sites, breaking the protein down into small peptides and amino acids. This sequence achieves a protein hydrolysis rate of up to 90.51%, providing the richest possible small-molecule precursors for subsequent hydrothermal recombination. The resulting hard carbon pore structure is uniform, exhibiting optimal electrochemical performance.
[0095] If the order is reversed (alkaline first, then flavor), as in Comparative Example 19, the alkaline protease can efficiently cleave the protein, but without the pre-disassembly by the flavor protease, some of the encapsulated cleavage sites cannot be fully utilized, resulting in a decrease in the overall degree of hydrolysis. If only a single flavor protease is used, the cleavage efficiency is insufficient, and the cleavage of large protein molecules is incomplete; if only a single alkaline protease is used, there is a lack of pre-loosening of the protein structure, limiting the hydrolysis efficiency. Both the single-enzyme and reversed-order schemes result in a lower specific capacity and initial coulombic efficiency of the final hard carbon compared to the two-enzyme stepwise scheme of this invention.
[0096] If the enzymatic hydrolysis temperature is too low, enzyme activity is inhibited, protein hydrolysis is incomplete, and pore development is poor after carbonization. If the temperature is too high, the enzyme protein denatures and becomes inactive, which also leads to a decrease in the degree of hydrolysis. A pH value deviating from the optimal range will also significantly reduce enzyme activity. If the enzyme dosage is too low, the hydrolysis rate is slow, making it difficult to achieve deep hydrolysis.
[0097] Although the performance of excessive enzyme dosage and excessive time is not significantly different from that of the optimal embodiment, excessive enzyme dosage (i.e., Comparative Examples 10 and 12) increases costs and excessive enzyme residue may introduce impurities; excessive time (i.e., Comparative Examples 15 and 17) has no significant gain and may cause microbial contamination.
[0098] Hydrothermal pretreatment is a key step in this invention. Below 120°C, the recombination reaction of small peptides and amino acids is insufficient, resulting in low cross-linking of the carbon skeleton and incomplete pore structure development. Above 180°C, excessive condensation and tar formation are easily triggered, leading to decreased porosity and carbon skeleton densification, which is detrimental to sodium ion storage. Too short a time results in insufficient reaction, while too long a time may cause pore structure collapse and increased energy consumption.
[0099] When the carbonization temperature is below 1000℃, carbonization is incomplete, resulting in high defect density and low initial coulombic efficiency. When the temperature is above 1600℃, the degree of graphitization is too high, the interlayer spacing decreases, some closed pores collapse, and the sodium ion diffusion kinetics deteriorate, leading to a decrease in capacity in the plateau region. The preferred temperature range of this invention, especially carbonization at 1300℃, can balance defects and graphitization, obtaining an ideal pseudo-graphite microcrystalline structure and abundant closed pores, achieving high reversible capacity and high initial coulombic efficiency.
[0100] The enzymatic hydrolysis followed by hydrothermal treatment method of this invention first hydrolyzes large protein molecules into small precursor molecules. These small molecules can then reorganize in an orderly manner during the subsequent hydrothermal process and self-encapsulate along the pores created by enzymatic hydrolysis to form a semi-closed structure, while avoiding the direct hydrothermal formation of tar from large molecules. The resulting hard carbon has a high specific surface area, a reasonable pore structure, and excellent electrochemical performance.
[0101] If the order is reversed, i.e., hydrothermal followed by enzymatic hydrolysis, the large protein molecules are already converted into tar during the hydrothermal process. The enzymes cannot act on these converted substrates, resulting in ineffective enzymatic hydrolysis, poor pore structure development, and a large amount of tar residue, leading to a significant decrease in electrochemical performance. If only enzymatic hydrolysis is performed without hydrothermal hydrolysis, the recombination process of small molecules is lacking, resulting in incomplete pore structure development and insufficient carbon skeleton stability. If only hydrothermal hydrolysis is performed without enzymatic hydrolysis, the large protein molecules directly produce a large amount of tar, the pore structure is uncontrollable, and both capacity and initial coulombic efficiency are low.
[0102] Table 3 shows the EDS elemental analysis results of Example 1 and some comparative examples. Comparing the EDS data of Example 1 with Comparative Examples 1 and 4, the hard carbon material obtained in Example 1 exhibits high carbon content and low oxygen content. In contrast, Comparative Example 4, lacking hydrothermal pretreatment, showed a significant decrease in carbon content (77.25%) and a substantial increase in oxygen content (20.27%). This confirms that the hydrothermal step effectively removes small peptides and amino acids produced by protease hydrolysis. Furthermore, almost no inorganic impurities such as K, Ca, and Zn were detected in Example 1. Based on the raw material characteristics, it can be reasonably inferred that under the optimized protease hydrolysis and hydrothermal synergistic process, most of the protein in the soybean residue raw material was hydrolyzed and effectively removed during the hydrothermal process, thus achieving the expected in-situ pore-forming effect. The structural characteristics of the final hard carbon material are consistent with its excellent electrochemical performance.
[0103] Table 3. EDS elemental analysis of Example 1 and the comparative example.
[0104] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications may be made without departing from the technical solutions described in the claims.
Claims
1. A method for regulating the pore structure of soybean residue-based hard carbon anode material using protease, characterized in that: Includes the following steps: (1) Mix dried soybean residue with water to form a paste, preheat and sonicate it, and then inoculate it with biological protease to carry out enzymatic hydrolysis; in step (1), the degree of hydrolysis of the material after enzymatic hydrolysis is ≥80%; the biological protease is inoculated sequentially with flavor protease and alkaline protease. (2) After the enzymatically hydrolyzed material is mixed with water, a hydrothermal reaction is carried out; (3) The hydrothermal reaction product is carbonized under an inert atmosphere to obtain a porous hard carbon material, which is then acid-washed to obtain a soybean residue-based porous hard carbon anode material.
2. The method according to claim 1, characterized in that: In step (1), the soybean residue is soybean residue derived from soybeans and their processed products, and its particle size is 3 to 75 μm; And / or, the protein content is 1% to 80%.
3. The method according to claim 1, characterized in that: In step (1), the mass concentration of the mixture of soybean residue and water is 5-15%; And / or, the heating temperature is 60~100℃; the heating time is 15~30 minutes; And / or, the ultrasonic frequency of the ultrasonic treatment is 20,000 ~ 50,000 Hz; the ultrasonic power is 100 ~ 600 W; and the ultrasonic time is 25 ~ 35 min.
4. The method as described in claim 1, characterized in that, In step (1), the enzymatic hydrolysis temperature of the flavor protease is 30-70℃ and the enzymatic hydrolysis pH is 5-7. The ratio of enzyme activity units to the weight of dried soybean residue is 2000U-4000U: 1g. The enzyme is inactivated after stirring for 1-6 hours. And / or, the enzymatic hydrolysis temperature of alkaline protease is 30 ~ 70℃ and the enzymatic hydrolysis pH is 7 ~ 10, the ratio of enzyme activity units to the weight of dried soybean residue is 2000U ~ 4000U : 1g, the enzyme is inactivated after stirring for 1 ~ 6 hours, and the pH is adjusted to 7.
5. The method according to claim 1, characterized in that: In step (2), the weight ratio of the enzymatically hydrolyzed material to water is 1:1 to 1:
5. And / or, the material after enzymatic hydrolysis is measured by oven-dry weight, with a drying temperature of 70 ~ 120 ℃ and a drying time of 1 ~ 5 days; And / or, the hydrothermal reaction temperature is 120 ~ 180℃, and the hydrothermal reaction time is 5 ~ 15 hours.
6. The method according to claim 1, characterized in that: In step (3), the hydrothermal reaction product is also dried. The residual protein and polypeptide in the dried hydrothermal reaction product account for 5-10% of the total mass. And / or, the heating rate for carbonization is 2 ~ 10 ℃ / min; the holding temperature is 1200 ~ 1500℃; and the holding time is 60 ~ 240 minutes. And / or, the acid solution used for pickling is hydrochloric acid; the solution concentration is 0.8 mol / L ~ 1.2 mol / L; the pickling time is 8 ~ 12 hours.
7. The method according to claim 1, characterized in that: Specifically, the following steps are included: S1. Add soybean residue to deionized water to prepare a mass concentration of 5-15%, and heat at 60-100℃ for 15-30 minutes; subject the resulting paste mixture to ultrasonic treatment at a frequency of 30000-50000Hz, a power of 100-300W, and a duration of 25-35 minutes. S2. Adjust the temperature of the paste mixture obtained in step S1 to 30-70℃ and the pH to 5-7, add flavor protease, with an enzyme activity unit: the ratio of dried soybean residue to 2000-4000U: 1g, stir for 1-6 hours, and inactivate the enzyme in a 90-100℃ forced-air drying oven for 10-30 minutes; then adjust the temperature to 30-70℃ and the pH to 7-10, add alkaline protease, with an enzyme activity unit: the ratio of dried soybean residue to 2000-4000U: 1g, stir for 1-6 hours, inactivate the enzyme in a 90-100℃ forced-air drying oven for 10-30 minutes, and adjust the pH to neutral; S3. Add the enzymatically hydrolyzed material to deionized water at a weight ratio of 1:1 to 1:5, stir evenly, transfer to a hydrothermal reactor, seal, and carry out hydrothermal reaction at 120 to 180°C for 5 to 15 hours. S4. After filtering, washing and drying the hydrothermal reaction product, the temperature is raised to 1200-1500℃ at a rate of 2-10℃ / min under an inert atmosphere and held for 60-240 minutes for carbonization. After acid washing and drying, porous hard carbon anode material is obtained.
8. The method according to claim 1, characterized in that: The specific surface area of the soybean residue-based porous hard carbon anode material is 3~40m². 2 / g; pore size distribution is mainly concentrated in 0.3 ~ 10nm; pore volume is 0.01 ~ 0.5cm³ 3 / g; average particle size is 1~20μm.
9. A soybean residue-based hard carbon anode material prepared by the method according to any one of claims 1 to 8.
10. The application of the soybean residue-based hard carbon anode material as described in claim 9 in a sodium-ion battery.
Citation Information
Patent Citations
A biomass hard carbon material and its preparation method and application in sodium ion battery
CN118270767B
Bean dreg-based hard carbon negative electrode material and preparation method and application thereof
CN118529713A
Method for preparing bean dregs-based nitrogen-boron co-doped porous carbon material
CN109336106A
Method for reducing content of protein in soybean dregs and preparing soybean peptide
CN109337950A
